A Systematic Literature Review on Indonesian Paradiplomacy (2018-2024) - Syuryansyah, Syuryansyah; Yunazwardi, Muhammad Iqbal; Nihayati, Arina (Journal of Islamic World and Politics, 2025)
Paradiplomacy in Indonesia has emerged as a strategy for local governments to enhance international cooperation. However, challenges such as regulatory constraints, lack of coordination with the central government, and misalignment with national foreign policy persist. This study systematically reviews articles indexed in the Scopus database to understand how subnational actors, such as local governments and non-state actors, utilize paradiplomacy to enhance their international relations. Using the Systematic Literature Review (SLR) method and the PRISMA approach, the initial search identified 17 articles, of which 14 were relevant and available in full text. The analysis revealed that research on Indonesia's paradiplomacy is relatively recent, with the earliest publication in 2018. Most studies focus on the relationships between local governments and international actors in economic, social, and cultural cooperation. Key challenges include bureaucratic issues and differing interests between central and local governments. This study found the urgent need to simplify regulations for regional governments to enhance diplomatic capacity at the local level and improve coordination between central and regional governments to increase the effectiveness of paradiplomacy. Transparency and accountability in international cooperation are also crucial to ensure benefits and prevent foreign investors from overshadowing local development priorities, thus ensuring fairness in the process.